Representação parental sobre a criança com altas habilidades ou superdotação - Braz, Paula Paulino (2022)
The family institution is the first social nucleus present in the life of the individual and contributes fundamentally as a central reference point in the process of human development. However, since it is formed by several members that acts in its subjective constitution, it is recommended that investigations involving the family delimit the focus on existing relationships. For this reason, the intention of this research was to investigate the representations about giftedness through the parental figure, that is, the father, mother or other responsible adult, who assumes the role of ensuring the care, education and development of children. Assuming that raising a child with atypical development is a challenge, the guiding question of the research was: what do parents think about the giftedness indicated in their children? The main objective was to know the parental representation about the giftedness displayed in their children. The specific objectives were: a) to verify and analyze the meanings attributed by the participants to the giftedness and; b) to point out how the parental representation about the giftedness can interfere in their children's lives. For this purpose, the research was set up with a descriptive approach and adopted the Collective Subject Discourse methodology for the treatment of the data collected in a qualitative and quantitative way, describing the individual’s thoughts collectively and evaluating the degree of sharing and distribution of this thought in the group. To collect the data, the semi-structured interview was used and the sample consisted of nine (9) mothers of preschool children with giftedness. The results indicated that parents' representation about giftedness involves knowledge produced by common sense, which changes in relation to the identification of giftedness in the child. Feelings such as fear and worry are present in the lives of these parents, especially by comparison with personal experiences lived, which may interfere with the child's education. Furthermore, it was possible to verify from the selected sample the recognition of characteristics of giftedness by the participants in themselves and in close relatives after the identification of the children. The social relevance of the research is justified by the importance of the family in the education and socio-emotional development of children. Thus, knowing the aspects involved in having children identified with high potential can contribute to advances in the field, in addition to guiding the development and implementation of work involving preschool children indicated with giftedness and their family, in schools and centers and associations that serv this public.